Monetary policy and economic performance - evidence from selected African countries - Fiador, Vera Ogeh Lassey (GSB: Faculty, 2016)
The main aim of this dissertation is to broaden the understanding of the monetary policy transmission mechanism as it operates in Sub-Saharan Africa. The ultimate goal is to aid in the appropriate design and implementation of monetary policy for the attainment of developmental goals. The dissertation empirically explores four issues on the pricing, behavioural and output implications of monetary policy. The four questions that the dissertation attempts to answer in Chapters Two to Five respectively are: 1) Does the effectiveness of monetary policy transmission depend on the financial development of an economy? 2) Can monetary policy be used as a tool in easing pressure on domestic currencies in the foreign exchange market? 3) Do banks engage in excessively risky behaviour when monetary policy is expansionary? 4) Does monetary policy influence aggregate variables like private capital formation, growth and their interrelationships? Chapter Two tests the completeness of the pass-through of the central bank policy rate to bank lending rates on one hand, and the interest rate pass-through as a function of the level of financial development on the other hand. The results show that the pass-through of central bank policy rate to bank lending rates is asymmetric for three Anglophone West African countries, namely: Gambia, Ghana and Nigeria, which are seeking to ascend onto a single monetary framework. However, there is no evidence that financial development affects the pass-through of monetary policy. These findings still prove relevant, especially with regard to the quest for effective monetary policy implementation and the ascension onto a single monetary framework by these 3 countries. The motivation for this study stemmed from policy discussions and academic debates on the premise that financial development is a key element in the pursuit of effective monetary policy implementation, focusing on the three Anglophone West African countries between 1975 and 2011. The study employs the bounds testing approach to cointegration, and the Autoregressive Distributed Lags (ARDL) by Pesaran et al., (2001). The findings show significant differences in the interest rate pass-through of the 3 countries studied. Ghana and Gambia were characterised by undershooting in the response of lending rates to monetary policy changes whilst Nigeria was characterised by overshooting in bank lending rates. Financial development proved significant in some, but not in all the cases, while economic growth proved mostly insignificant in the transmission of the policy rate to bank lending rates In Chapter Three, we show that contractionary monetary policy of high interest rates is able to correct disequilibrium in the foreign currency market in selected countries in Sub-Saharan Africa (SSA). The chapter also provides empirical evidence about the impact of macroeconomic fundamentals on the domestic foreign exchange market. The study assesses the impact of monetary policy on foreign exchange market pressure (EMP) in developing country contexts focusing on some selected countries in SSA. EMP is the sum of exchange rate depreciation and change in foreign reserves that is required to restore equilibrium to the domestic foreign exchange market. The study was motivated by the fact that most of the SSA countries are developing economies that have negative net export positions and stand to lose significantly from consistently deteriorating foreign exchange positions. This study thus sought to measure the ability of monetary policy to significantly address currency pressures that arise from trading on the global market. The hypothesis that a tighter monetary policy stance can lend strength to a currency was tested in this study using Generalised Methods of Moments (GMM) estimation in a dynamic panel setting. Data on 20 SSA economies for which data were available for the period 1991 to 2010 are used. The study found a negative and significant relationship between monetary policy and EMP, implying that contractionary monetary policy can ease EMP.